Oral candidal colonization in immunocompromised patients - Zahraa S. Kasim; Manahil M. Yehia (University of Mosul, 2013)
Objective: 1. To identify Candida species isolated from saliva of predicatively immunocompromised (cancer, diabetic) patients and control group. 2. To test the susceptibility of all the isolated yeasts against 6 antifungal agents, namely amphotericin B, nystatin, fluconazole, ketoconazole, voriconazole and itraconazole. 3. Then to compare the growth and density of yeasts from immunocompromised patients to those from healthy control group. Patients and Methods: This study included 120 saliva samples from immunocompromised patients, 60 of them with cancer and under treatment, the other 60 patients have uncontrolled diabetes mellitus, attending the Al-Wafa'a Center for diabetic patients and the consultative clinic of Oncology and Nuclear Medicine Hospital. The clinical specimens were collected during the period from January-June 2011. In addition to 60 saliva samples from a healthy individuals. The identification of the isolated yeasts was carried by fluorescent and/or light microscope, culture on different types of media, biochemical tests and API-20 C system. Susceptibility test to six antifungal agents was prepared for each isolate. Results: Eighty seven (72.5%) patients showed the presence of yeasts in their saliva in comparison to 18(30%) from the control group. Eighty four isolates from genus Candida identified into 8 species mainly C. albicans. The isolates showed the best susceptibility to amphotericin B. Conclusions: A higher frequency of yeasts were detected in the immunocompromised patients in comparison to the control group. This is considered a risk factor for infection. Candida albicans is the main isolate but there was a shift to non -albicans Candida spp. in immunocompromised patients. This means that are more resistant to antifungal agents.